2017 IEEE Wireless Communications and Networking Conference Workshops (WCNCW) 2017
DOI: 10.1109/wcncw.2017.7919040
|View full text |Cite
|
Sign up to set email alerts
|

Low-Complexity Puncturing and Shortening of Polar Codes

Abstract: Abstract-In this work, we address the low-complexity construction of shortened and punctured polar codes from a unified view. While several independent puncturing and shortening designs were attempted in the literature, our goal is a unique, low-complexity construction encompassing both techniques in order to achieve any code length and rate. We observe that our solution significantly reduces the construction complexity as compared to state-of-the-art solutions while providing a block error rate performance co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 12 publications
0
59
0
Order By: Relevance
“…In puncturing, the untransmitted code bits are treated as erased at the decoder, while shortening introduces a sub-code imposing the untransmitted code bits to assume a fixed value, typically zero, such that their value is already known by the decoder. It has been observed that for polar codes, shortening works better for high rates, and puncturing for low rates [31].…”
Section: Rate Matchingmentioning
confidence: 99%
See 1 more Smart Citation
“…In puncturing, the untransmitted code bits are treated as erased at the decoder, while shortening introduces a sub-code imposing the untransmitted code bits to assume a fixed value, typically zero, such that their value is already known by the decoder. It has been observed that for polar codes, shortening works better for high rates, and puncturing for low rates [31].…”
Section: Rate Matchingmentioning
confidence: 99%
“…Shortening, on the contrary, improves the bit channel reliabilities by introducing overcapable bits, i.e. bits with conceptually infinite reliability that are always correctly decoded [31]. However, code bits in the matching pattern must depend on frozen bits only, which forces to freeze the most reliable bit-channels worsening the error correction capabilities of the code.…”
Section: Rate Matchingmentioning
confidence: 99%
“…However, the codeword length was limited to N = l n . For the sake of obtaining arbitrary codeword lengths, puncturing and shorterning techniques were exploited in [50]- [52], while multi-kernel polar codes, invoking multiple l-bit kernels, were conceived in [53], [54]. Nonetheless, in this paper, we will focus on Arikan's polar codes.…”
Section: B Non-arikan Polar Codesmentioning
confidence: 99%
“…Numerous rate-matching schemes for polar codes have been widely studied in the literature [5]- [17]. Among them, puncturing and shortening have been commonly studied.…”
Section: Introductionmentioning
confidence: 99%